The Dialectic of Contemporary Thought of The Muhammadiyah Economic Movement - Imamul Hakim (Universitas Alma Ata, 2019)
Muhammadiyah is one of the largest religious organization in Indonesia that has stood more than a century and became an organization with the world's greatest asset, however up to now Muhammadiyah still does not have a definite format of economic movement. The dialectic of Muhammadiyah economic movement remains a fascinating debate. This study aims to examine the ideas of Muhammadiyah's economic format that have been outlined by Muhammadiyah figures, experts, and scholars in the form of writing to look for the intersection of thought into a single entity the main idea of Muhammadiyah Economic Format. This research using the method of the library research with the source data that is be retrieved from the secondary data that have been written by scholars, scientists, and experts of the Muhammadiyah economic movement have ever written about the format of Muhammadiyah economic movement. The results show that there are three groups of main ideas about the format of the Muhammadiyah economic movement, that is; Firstly, Incorporated Movement, is incorporated in the management merger business which it strengthened networking either in vertical or horizontally. Secondly, Community economic empowerment movement, This movement emphasizes full structural involvement in economic empowerment by providing information on market opportunities, capital, business training, financial management and making business innovations. Thirdly, the Comprehensive Economic Movement, namely; the Economic Movement that integrates Incorporated and Empowerment. Muhammadiyah's economic movement needs to be built in two directions by combining Incorporated and Empowering, through structuring and merging Muhammadiyah's business entities with economic empowerment of Muhammadiyah citizens.